The Impact of Internal Marketing on the Contextual Performance of Teachers - ناصر الرفاعي محمد (Journal of Libyan Academy Bani Walid, 2025)
The study examined the impact of internal marketing on the contextual performance of teachers at Al Wadi Al Akhdar School in Bani Walid, based on the importance of the human element in the success of educational institutions. The researcher used the descriptive analytical approach, and relied on a questionnaire that included 36 parameters to measure the dimensions of internal marketing represented by training, incentives, empowerment, and internal communication, and link them to the contextual performance variable represented by organizational citizenship and organizational commitment. The results showed that the level of internal marketing in the school was low with an overall average (2.57), while contextual performance was average (2.68). Statistical analysis also showed a strong direct relationship and statistical significance between internal marketing and contextual performance, as internal marketing explains about 82% of changes in parameter performance. The study concluded that developing training programs, improving the incentive system, granting broader powers to teachers, and enhancing internal communication can contribute significantly to raising the level of contextual performance and enhancing institutional belonging and loyalty, which reflects positively on the quality of the educational process and the stability of teaching staff.